Renewable energy: A way for a sustainable development in Romania. Issue 11 (2nd November 2017) - Aceleanu, Mirela Ionela; Șerban, Andreea Claudia; Pociovălișteanu, Diana Mihaela; Dimian, Gina Cristina
ABSTRACT: The development of renewable energy sources is justified by keeping a clean environment, by assurance of energy security, by job creation, all these contributing to sustainable economic growth. The paper presents the development level of renewable energy sector in Romania and the benefits of its extension, starting from the potential of Romania in this field. From natural point of view, Romania has a high potential for development of renewable energy, in the hydro, wind, solar, geothermal, and biomass fields. The research results show that even if there are certain limitations in expansion of this field, the natural potential and the advantages obtained by development of renewable energy sources require continued investments and public–private efforts to support it.